GE_GERICHTE P/11362/2017 vom 4. Dezember 2019 - GE Cour de justice (2019)
SÉQUESTRE(MESURE PROVISIONNELLE);SUPPRESSION(EN GÉNÉRAL);ESCROQUERIE;CORRUPTION ACTIVE D'AGENTS PUBLICS ÉTRANGERS | CPP.197.al1.letb; CPP.197.al1.letc; CPP.267.al1; CP.146; CP.322septies